Exploration of AI-enabled Contents for Undergraduate Cyber Security Programs - Ramoni Lasisi; Matthew Menia; Zachary Farr; Corey Jones (Proceedings of the International Florida Artificial Intelligence Research Society Conference)
This paper investigates the AI courses and/or topics that are needed to enhance cybersecurity education towards preparation of the future AI-enabled cybersecurity leaders.~We found that, although sophisticated cyber crimes are now been perpetrated using AI technologies, AI courses and topics are currently missing in virtually all the undergraduate cybersecurity programs we reviewed.